A Comparison of The Effectiveness of The Tera Gymnastics Breathing Technique with Deep Breathing Techniques on Reducing Labor Pain - Ryka Juaeriah; Yuliana; Gemilang Rahma Annisa (STIKes Budi Luhur Cimahi, 2025)
The most common problem that arises in maternity mothers is labor pain. Pain during labor accompanied by fear will slow down the labor process. Labor pain will cause hyperventilation, increase oxygen consumption, cause respiratory alkalosis, vasoconstriction of blood vessels in the uterus and acidosis in the fetus. Increasing noradrenaline will lower blood to the placenta and decrease uterine contractions, thereby interfering with the safety of the mother and fetus and the success of vaginal partus. Tera gymnastics can stimulate the heart's ability to pump blood to meet oxygen needs so that the heart works with relaxation, resting pulse, and blood pressure becomes stable. The purpose of this study was to determine the comparison of the effectiveness of deep breathing and tera gymnastics breathing techniques on pain reduction during the first childbirth. This study uses a quasi-experimental design with two groups pretest-posttest design. The research was carried out at TPMB